THE CONTROVERSY OVER THE DETECTION OF PHOSPHINE (PH3) IN VENUS' ATMOSPHERE: A STUDY USING ALMA DATA - Salsabila, Salma
Venus, Earth’s closest neighbour, has many similarities in terms of mass and diameter compared to Earth, as well as geological characteristics. However, in terms of atmosphere, Venus is very different from Earth. Venus has an atmosphere much thicker than Earth’s, with pressure at the surface reaching 92 bar and extremely hot temperatures reaching 735 K. Therefore, Venus is thought to have no life on its surface. However, recently, Greaves et al. (2020) through observations with the JCMT and ALMA radio telescopes at millimeter wavelengths claimed the detection of phosphine molecules (PH3) in the high cloud layers in the Venus stratosphere. Analysis and modeling shows that the abundance of PH3 is relatively small, around ? 20 ppb, but its origin cannot be explained by abiotic sources alone, for example from photochemical reactions, volcanic eruptions, and so on. This then raises the hypothesis of the possibility of a biotic source such as on Earth. In this Final Project, data processing from observations of Venus by ALMA in March 2019 at a frequency of 266944,662 MHz is carried out, which is thought to contain spectral features of PH3 in the atmosphere of Venus. The results of the analysis show that the detection of PH3 cannot be confirmed from these data alone. Additional observations are needed to confirm the presence of PH3 in Venus’ atmosphere.